1993
DOI: 10.1051/jp4:1993107
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically cross-linked micellar solutions : microstructure and properties of the solutions

Abstract: solutions that contained microemulsion droplets. It was found that the viscosity of these solutions could become significantly enhanced upon its addition. SANS and light scattering data of these solutions showed that the size of the droplets did not change. The scattering data of the cross -linked micelles could be fitted with a model for hard spheres that induded an additional attractive term. The shear moduli which were determined from the viscoelastic solutions are consistent with the scattering data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 1 publication
3
44
0
Order By: Relevance
“…The volume fraction depends on the molar concentration of the vesicle dispersions. This has been similarly observed in the case of enhancing the viscosity of microemulsions by the addition of hydrophobically end-capped polymers [25]. The mean spacing between the bilayers of the vesicles db is equal to d-2R.…”
Section: Resultssupporting
confidence: 58%
“…The volume fraction depends on the molar concentration of the vesicle dispersions. This has been similarly observed in the case of enhancing the viscosity of microemulsions by the addition of hydrophobically end-capped polymers [25]. The mean spacing between the bilayers of the vesicles db is equal to d-2R.…”
Section: Resultssupporting
confidence: 58%
“…The scaling is for both cases relatively similar and only slightly more concentration dependent for the case of ethylene glycol. From a simple network theory [27][28][29] one can relate the shear modulus G 0 (that in our case should be well approximated by G (1 Hz)) directly to the number of network points by:…”
Section: Variation Of the Organic Solventmentioning
confidence: 99%
“…It was found that these polymers form a transient network of interconnected micelles in water. [1][2][3][4]8,[10][11][12][13][14][15] The hydrophobic end groups function as ''stickers'' and the viscosity increase can be correlated to their length. 1,4,8,13,15 In the case of linear polymers, it is obvious that one polymer molecule can link not more than two micelles.…”
Section: Introductionmentioning
confidence: 99%